Bloodlands : Europe between Hitler and Stalin - Snyder, Timothy (New York : Basic Books, 2010)
This book discusses how Poland, Ukraine, the Baltics and Belarus were victimized by two mass murderers with competing utopian visions.
Hitler and Stalin -- The Soviet famines -- Class terror -- National terror -- Molotov-Ribbentrop Europe -- The economics of apocalypse -- Final solution -- Holocaust and revenge -- The Nazi death factories -- Resistance and incineration -- Ethnic cleansings -- Stalinist antisemitism -- Humanity.
Includes bibliographical references (p. 423-462) and index.
Keywords: Stalin, Joseph, -- 1879-1953.; Hitler, Adolf, -- 1889-1945.; Genocide -- Europe, Eastern -- History -- 20th century; Massacres -- Europe, Eastern -- History -- 20th century; Holocaust, Jewish (1939-1945); World War, 1939-1945 -- Atrocities; Europe, Eastern -- History -- 1918-1945.; Soviet Union -- History -- 1917-1936.; Germany -- History -- 1933-1945.